Telemetria com o uso de arduino em lançamento de foguetes no ensino médio: uma metodologia alternativa para ensinar cinemática no lançamento oblíquo de foguetes de garrafa PET - PAIVA, Annatanael Silva (2021)
This work presents an educational product that brings together a didactic sequence based on the Theory of Meaningful Learning that relates the thematic of concepts seen in the kinematics of oblique launch with the experimental practice through PET bottle rocket launch telemetry. The main objective of this research is to describe the preparation of an experimental kit for launching rockets from PET bottles using the arduino through five stages of a didactic sequence that starts from an investigation of students' prior knowledge about the concepts related to kinematics to the demonstration that the teaching of Physics can be promoted in an organized way, translating its phenomena into interesting problems for students, possible to be solved, observed in practice. This proposal was developed in partnership with first-year students from the Instituto Federal de Ciência e Tecnologia do Maranhão (IFMA), located in the city of Barra do Corda - MA. Projectile launches were carried out outside the school's boundaries, according to the safety requirements, in which in one of them, the students could observe a good accuracy for the calculation of the range when compared to the real trajectory by the movement of the rocket with its ideal path, as well as a more detailed understanding of other concepts inherent to oblique motion such as acceleration and the action of gravitational force. We evaluated the proposed practice in the different stages of didactic sequence and found that effective participation added to the productivity of students, we obtained evidence of learning, as it was possible to identify difficulties and develop how students can overcome this challenge. Therefore, with this educational product, we aim to make it an instructional material for use in any educational environment that motivates and enriches classes on the proposed topic.